Assessment of the maxilla‐mandible‐nasion angle in normal and aneuploid foetuses in the first trimester of pregnancy. Issue 2 (1st December 2020) - Tekesin, Ismail; Graupner, Oliver
Abstract: Purpose: This retrospective study aims to determine whether the maxilla‐mandible‐nasion (MMN) angle can be reliably measured in the first trimester, to describe normal ranges, and to determine if significant changes occur in foetuses with aneuploidies. Methods: The MMN angle was measured in stored 2D‐ultrasound images of 200 normal fetal profiles between 11 +0 and 13 +6 weeks of gestation. Each image was analyzed by two observers at two independent time points. Bland‐Altmann analysis was performed to evaluate the reliability of the measurements. Additionally, the MMN angle was measured on sonograms from 140 aneuploid foetuses. Results: The mean MMN angle in normal foetuses from 11 to 14 weeks of gestation was 15.4°. Reliability of the measurement was high when repeatedly measured by the same observer (ICC = 0.92 and 0.82) and between two observers (ICC = 0.77 and 0.63). Average MMN values in foetuses with trisomy 21, 13, and Turner syndrome were significantly higher than those measured in normal foetuses. The highest differences were observed in foetuses with trisomy 13. Among those, 62% had an MMN angle above the 95th percentile and 92% above the normal mean. Conclusion: The MMN angle can be reliably measured in early pregnancy and is abnormal in about 60% of foetuses with trisomy 13.